If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6c + 2 = 126 Reorder the terms: 2 + 6c = 126 Solving 2 + 6c = 126 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 6c = 126 + -2 Combine like terms: 2 + -2 = 0 0 + 6c = 126 + -2 6c = 126 + -2 Combine like terms: 126 + -2 = 124 6c = 124 Divide each side by '6'. c = 20.66666667 Simplifying c = 20.66666667
| 2x^3=375 | | 2x^3-10x^2+6x+1=0 | | 5x+8=-69-6x | | 8x=180-10x | | 7+8x=-21+x | | m^3-6m^2+18.5=0 | | 2.5y=4 | | 36sinx=3 | | 2y/=4 | | 9y+6=12 | | (X-8)*(7-sinx)+7-sinx=0 | | 64+28= | | 2n+3k=21 | | 16+16+16+16= | | 93=7x-3 | | 16=3(4x+2)-2 | | 108-24= | | 8x+6=2x-30 | | 6m+3=33 | | 9x-8=5x+5 | | 0.5*n(n-3)=54 | | -3x-17=-2 | | 8x-2+3x=13x+8 | | -11=x+16 | | 11w=3520 | | z-3=30 | | 10c=70 | | 5w+6=9w+3 | | q-6=6 | | 4=m-2 | | 12+g=16 | | t+15=19 |